Diabetes oxidative stress and dietary antioxidant - Preedy, Victor R. (Elsevier Science, 2014)
Diabetes: Oxidative Stress and Dietary Antioxidants bridges the trans-disciplinary divide among diabetologists, endocrinologists, and nutritionists in understanding and treating diabetes. The book covers, in a single volume, the science of oxidative stress in diabetes and the potentially therapeutic use of natural antioxidants in the diet or food matrix. The processes within the science of oxidative stress are described in concert with other processes such as apoptosis, cell signaling, receptor-mediated responses and more. This approach recognizes that diseases are usually multifactorial and that oxidative stress is a single component of this. Pharmacological treatments for diabetes are commonly marked by unwanted side effects, leading to treatment efforts using naturally occurring substances. But a plant-based approach alone is not sufficient; understanding the processes inherent in the oxidative stress of diabetes is vital for clinical workers, dietitians, and nutritionists. This translational work provides that understanding. The book begins by covering the basic biology of oxidative stress from molecular biology to imaging in relation to diabetes. There are chapters on neuropathy, nephropathy, atherosclerosis, cardiomyopathy, and retinopathy. The book then moves on to antioxidants in foods, including plants, components of the diet, and their relevance to diabetes.--Publisher.
Includes index.
Keywords: diabetes mellitus; diabetologie; oxidační stres; antioxidanty; diabetology; oxidative stress; antioxidants; elektronické knihy; electronic books